Exome Sequencing for Prenatal Diagnosis in Nonimmune Hydrops Fetalis. Issue 3 (March 2021) - Sparks, Teresa N.; Lianoglou, Billie R.; Adami, Rebecca R.; Pluym, Ilina D.; Holliman, Kerry; Duffy, Jennifer; Downum, Sarah L.; Patel, Sachi; Faubel, Amanda; Boe, Nina M.; Field, Nancy T.; Murphy, Aisling; et al.
Abstract : (Abstracted from N Engl J Med 2020;383:1746–1756) Nonimmune hydrops fetalis (NIHF) is a condition complicating approximately 1 in 1700 to 3000 pregnancies where the fetus develops an overload of fluid, causing a wide range of outcomes such as stillbirth, preterm birth, neonatal complications, or neonatal death. Standard genetic testing with microarray or karyotype identifies a genetic cause of hydrops approximately only 25% of the time.